Population modeling to inform management and recovery efforts for lake sturgeon, Acipenser fulvescens. (9th February 2022) - Vaugeois, Maxime; Venturelli, Paul A.; Hummel, Stephanie L.; Forbes, Valery E.
Abstract: Lake sturgeon ( Acipenser fulvescens ) populations have significantly declined across their historic range, in large part due to anthropogenic impacts that have likely been exacerbated by the life‐history traits of this slow‐growing and long‐lived species. We developed a population model to explore how Contaminants of Emerging Concern (CECs) impact lake sturgeon populations. We explored how different physiological modes of action (pMoAs) of CECs impacted population abundance and recovery and how different simulated management actions could enable recovery. We first estimated the impacts on population abundance and recovery by comparing the trajectory of an unexposed population to a population that had been exposed to a CEC with a specific pMoA after the end of the exposure. We then predicted how different management actions would impact population recovery by comparing the trajectories of an unexposed population to an exposed population for which a management action started at a fixed time without discontinuation of the exposure. Our results predicted that the individual‐level pMoA of CECs has an important impact on population‐level effects because different stressor's pMoA impacts the life‐history traits of sturgeon differently. For example, the feeding and reproduction pMoAs caused the strongest and weakest population declines, respectively. For the same reason, pMoA also impacted recovery. For example, recovery was delayed when the pMoA was growth, maintenance, or feeding, but it was immediate when the pMoA was reproduction. We found that management actions that increased the egg survival rate or the stocking of fingerlings resulted in faster and stronger recovery than management actions that increased the juvenile or adult survival rate. This result occurred because the first two management actions immediately impacted recruitment, whereas the impact was delayed for the last two. Finally, there was greater potential for recovery when management action targeted eggs and fingerlings because these life stages have lower natural survival rates. Integr Environ Assess Manag 2022;18:1597–1608. © 2022 Society of Environmental Toxicology & Chemistry (SETAC). This article has been contributed to by US Government employees and their work is in the public domain in the USA. KEY POINTS: The individual‐level physiological mode of action of a stressor is important to forecast its effects at the population level and select the most appropriate management strategy. Management actions that increased egg survival rate or the stocking of fingerlings resulted in faster and stronger recovery than management actions that increased juvenile or adult survival rate. There is a greater potential for recovery when management actions target eggs and fingerlings because these life stages have lower natural survival rates.